THE SYNERGY BETWEEN DIPLOMACY AND INTERNATIONAL RELATIONS THEORIES - Ergasheva Feruzabonu Odiljonovna (TADQIQOTLAR.UZ, 2025)
The intricate dance of global politics is shaped by a dynamic interplay between diplomacy and the theories of international relations. Diplomacy, the art of negotiation and  communication  between  states,  serves  as  a  practical  application  of  various theoretical  frameworks  that  seek  to  explain  and  predict  international  behavior. Understanding this synergy is essential for both scholars and practitioners in the field.